Efforts To Increase Students' Learning Motivation Through Ice Breaking In Pjok Learning - Hakim, Hikmad; Awaluddin, Awaluddin (SHOOTING: Journal of Sport, Health, and Education, 2024)
This research applies the Classroom Action Research (PTK) method using a cycle approach in an effort to increase student learning motivation in Physical Education, Sports and Health (PJOK) subjects. This research consists of two cycles with stages of planning, implementation, observation, and reflection. In Cycle I, the average student learning motivation reached 45.31%, while in Cycle II, the average learning motivation increased significantly to 70.62%. This increase of 25.31% reflects positive changes in students' interest and enthusiasm for learning. The results obtained indicate that the intervention in the form of using “ice breaking” and refreshment during learning in Cycle II successfully stimulated students' interest and motivation. This increase in learning motivation also reflects the effectiveness of the emphasis on more interesting and participatory learning. These positive results illustrate the impact of the improvements and efforts made in Cycle II in creating a better learning environment. This research provides a positive view of the use of PTK methods with a cyclical approach and the implementation of “ice breaking” in increasing student learning motivation in PJOK subjects. The implications of these findings underscore the importance of innovative approaches in learning to achieve more optimal learning objectives.